Element Distribution and Migration Behavior in the Copper Slag Reduction and Separation Process - Zuo, Zongliang; Feng, Yan; Luo, Siyi; Dong, Xinjiang; Li, Xiaoteng; Ren, Dongdong; Yu, Qingbo; Guo, Jianxiang (Frontiers in Energy Research, 2021)
Copper slag is a solid pollutant with high recyclability. Reduction and separation are regarded as effective disposal methods. However, during the melting process, the separation and migration behavior of elements in the copper slag is complicated. Thus, the formation of pollutants cannot be controlled merely by optimizing the operation parameters. The elemental distribution and migration behavior are discussed in this work. In reduction experiments, the copper slag smelting liquid was divided into three layers: a reduction slag layer, a reactive boundary layer, and an iron ingot layer. Reduction slag and ingot iron were on the top and bottom of the liquid, respectively. Residual carbon oozed at the interface. C can react with reducible “O” atoms, which exist in 2FeO·SiO2, Fe3O4, and CuO. Meanwhile, CO was generated and overflowed from the liquid layer. After reduction by C or CO, metallic iron and copper were produced and migrated to the iron ingot layer. In the liquid, S gradually diffused into the upper layer. Some of the ZnO and CuS spilled from the liquid into the flume. After reduction, CaO·SiO2 was generated and moved to the upper layer.